NEYROPEDAGOGIK YONDASHUVLAR ASOSIDA OLIY TA‘LIMDA MOTIVATSIYANI OSHIRISHNING PSIXO-BIOLOGIK MEXANIZMLARI - O‘ktamova Shahrizoda Shavkatovna, (TADQIQOTLAR, 2025)
Abstract.  This  article  scientifically  and  theoretically  analyzes  the psychobiological mechanisms of increasing students' motivation for learning in higher education based on neuropedagogical approaches. The study highlights the importance of brain activity, emotional state, attention processes, and the dopamine system in the learning process, and shows the role of neurophysiological factors in the formation of motivation.  It  also  substantiates  the  effectiveness  of  neurodidactic  methods  that enhance  cognitive  activity  in  students,  multimodal  educational  technologies, psychological  training  that  reduces  stress,  and  educational  strategies  adapted  to individual neurotypes. The article is aimed at improving scientific and methodological approaches to increasing motivation in the higher education system and explores the possibilities of sustainable development of students' learning activity.